Third-party fecal microbiota transplantation following allo-HCT reconstitutes microbiome diversity - DeFilipp, Zachariah; Peled, Jonathan U.; Li, Shuli; Mahabamunuge, Jasmin; Dagher, Zeina; Slingerland, Ann E.; Del Rio, Candice; Valles, Betsy; Kempner, Maria E.; Smith, Melissa; Brown, Jami; Dey, Bimalangshu R.; et al. (Blood advances, 2018)
We hypothesized that third-party fecal microbiota transplantation (FMT) may restore intestinal microbiome diversity after allogeneic hematopoietic cell transplantation (allo-HCT). In this open-label single-group pilot study, 18 subjects were enrolled before allo-HCT and planned to receive third-party FMT capsules. FMT capsules were administered no later than 4 weeks after neutrophil engraftment, and antibiotics were not allowed within 48 hours before FMT. Five patients did not receive FMT because of the development of early acute gastrointestinal (GI) graft-versus-host disease (GVHD) before FMT (n = 3), persistent HCT-associated GI toxicity (n = 1), or patient decision (n = 1). Thirteen patients received FMT at a median of 27 days (range, 19-45 days) after HCT. Participants were able to swallow and tolerate all FMT capsules, meeting the primary study endpoint of feasibility. FMT was tolerated well, with 1 treatment-related significant adverse event (abdominal pain). Two patients subsequently developed acute GI GVHD, with 1 patient also having concurrent bacteremia. No additional cases of bacteremia occurred. Median follow-up for survivors is 15 months (range, 13-20 months). The Kaplan-Meier estimates for 12-month overall survival and progression-free survival after FMT were 85% (95% confidence interval, 51%-96%) and 85% (95% confidence interval, 51%-96%), respectively. There was 1 nonrelapse death resulting from acute GI GVHD (12-month nonrelapse mortality, 8%; 95% confidence interval, 0%-30%). Analysis of stool composition and urine 3-indoxyl sulfate concentration indicated improvement in intestinal microbiome diversity after FMT that was associated with expansion of stool-donor taxa. These results indicate that empiric third-party FMT after allo-HCT appears to be feasible, safe, and associated with expansion of recipient microbiome diversity. This trial was registered at www.clinicaltrials.gov as #NCT02733744. •The administration of third-party FMT capsules early after allogeneic HCT is feasible and appears safe.•FMT is associated with early expansion of microbiome diversity in transplant recipients. [Display omitted]